2007
DOI: 10.1021/ja070273v
|View full text |Cite
|
Sign up to set email alerts
|

Template-Directed Oligonucleotide Strand Ligation, Covalent Intramolecular DNA Circularization and Catenation Using Click Chemistry

Abstract: The copper-catalyzed azide-alkyne cycloaddition reaction has been used for the template-mediated chemical ligation of two oligonucleotide strands, one with a 5'-alkyne and the other with a 3'-azide, to produce a DNA strand with an unnatural backbone at the ligation point. A template-free click-ligation reaction has been used for the intramolecular circularization of a single stranded oligonucleotide which was used as a template for the synthesis of a covalently closed DNA catenane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
234
0
10

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 257 publications
(245 citation statements)
references
References 21 publications
1
234
0
10
Order By: Relevance
“…68 Oxime circularization was also used for circularization of RNA, although only small circles (tetramers) were prepared. 69 Other circularization procedures involve copper catalyzed azide alkyne cycloaddition (CuAAC) 70,71 (Fig. 1f), strategies for photoligation, 72 or conjugation of metal binding ligands such as terpyridine to the 5 0 -and 3 0 -end of the oligonucleotide to be circularized (Fig.…”
Section: Chemical Strategiesmentioning
confidence: 99%
“…68 Oxime circularization was also used for circularization of RNA, although only small circles (tetramers) were prepared. 69 Other circularization procedures involve copper catalyzed azide alkyne cycloaddition (CuAAC) 70,71 (Fig. 1f), strategies for photoligation, 72 or conjugation of metal binding ligands such as terpyridine to the 5 0 -and 3 0 -end of the oligonucleotide to be circularized (Fig.…”
Section: Chemical Strategiesmentioning
confidence: 99%
“…One important factor for consideration when making DNA nanodevice is the preparation yield 28,31 . Since D2Cs produced in our approach do not appear to be based on extensive base-pairing interactions, their preparation may suffer from lower reaction yield.…”
Section: Articlementioning
confidence: 99%
“…We chose this highly selective and efficient reaction for nucleic acid ligation for several reasons: (i) alkynes and azides can readily be attached to nucleic acids; (ii) the reaction proceeds efficiently in aqueous media; (iii) it can be triggered by addition of Cu I ; and (iv) the resultant triazole ring is chemically robust and generally considered to be non-toxic. When we started this project ourselves and others had already shown that this reaction to be compatible with DNA (Gartner et al 2003;Kanan et al 2004;Kumar et al 2007). The new challenge was to design a biocompatible triazole linkage that can be tolerated by DNA and RNA polymerase enzymes in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%